Surah Al-Nisa’: some lessons for Muslim business leaders based on the works of Khaled and Khan = Surah Al-Nisa : beberapa pelajaran untuk pemimpin perniagaan Muslim berdasarkan tafsiran Khaled dan Khan - Fontaine, Rodrigue Ancelot Harvey (IIUM Press, 2018)
This study looks at sūrah al-Nisa’ (Chapter The Women)and draws some lessons for Muslim business leaders. The focus is on Muslim business leaders as they have the power and authority to transform the corporate culture of their organisations. The author compared and contrasted the works of Khaled and Khan. Although the general theme of the sūrah is justice, this author focuses on ihsan. Generally, people need to have ihsan towards one another (4:36), whether Muslims or non-Muslims. Extrapolating from this principle, this sūrah teaches us that managers need to have ihsan towards their subordinates and vice-versa. The complexity of the concept of ihsan is explored. Although ihsan is linked to taqwa (piety), it is also linked to remembering death and resurrection. The author tried two experiments, derived from the work of Kübler-Ross, to demonstrate how developing a culture of ihsan is possible. The findings state that developing a culture of ihsan is straightforward but facilitators need to have a counsel-ling background to address participants’ concerns in the right manner.